Belchior and the political criticism in the song "My Brazilian Cordial" - Campos, Melissa Campos Oliveira Cavalcante (Seven Editora, 2023)
This article analyzes the political criticism in the song "Meu cordial brasileiro", by the singer and composer from Ceará, Belchior. First, we address the relationship between music and the dictatorial context in Brazil. Then, we investigated Belchior’s trajectory through studies about him - from his birth in Sobral, his experience in Fortaleza as part of the generation of artists and intellectuals known as Pessoal do Ceará, and in other places in Brazil - and found that the artist was censored and that he composed lyrics that contained criticism of the regime. To analyze the lyrics of the song "Meu cordial brasileiro", we based ourselves on the dialogue of the works of authors on discourse analysis and linguistics, among them, Garcia, Menezes, Fiorin, Maingueneau and Koch, using the terms "metaphor", "intertextuality" and "irony". In the analysis, we identified argumentative and textual elements that allow us to verify how this song contests the political regime. The study has broadened our knowledge of our artistic, cultural and political history. DOI:https://doi.org/10.56238/sevened2023.004-040